MOTIVASI KERJA PEGAWAI PADA KANTOR UNIT PELAKSANAAN TEKNIS PENGEMBANGAN KEGIATAN BELAJAR PENDIDIKAN NON FORMAL DAN INFORMAL PROVINSI SULAWESI TENGAH - Patoding, Hanri (Katalogis, 2017)
One of the most important assets of the organization can not be separated from the employee's performance. To obtain good performance, it is necessary to improve employee motivation. In developing the organization, people often focused on how to develop the business, while on the management of human resources is still less attention.This study was conducted to determine howÂ  the Employee Work Motivation In Learning Activity Implementation Unit Office of Non-Formal and Informal Education In the province of Central Sulawesi. Researchers used the theory of Frederick Herzberg and The basis of this research is qualitative descriptive type of research. The technique used in data collection is observation, in-depth interviews and documentation. Then the data and the interviews were analyzed by descriptive qualitative. The results showed that, motivation of employees working in On Learning Activity Implementation Unit Office of Non-Formal and Informal Education In the province of Central Sulawesi has been very good. It is based on several aspects of the increased motivation of employees working on extrinsic and intrinsic factors.